2016
DOI: 10.1039/c5fo01252j
|View full text |Cite
|
Sign up to set email alerts
|

Dose-related effects of ferric citrate supplementation on endoplasmic reticular stress responses and insulin signalling pathways in streptozotocin–nicotinamide-induced diabetes

Abstract: Diabetic patients are at high risk of developing anemia; however, pharmacological doses of iron supplementation may vary greatly depending on diabetes-related complications. The aim of this study was to investigate the dose-dependent effect of iron on glucose disposal with a special focus on endoplasmic reticular (ER) stress, iron metabolism, and insulin signalling pathways. Diabetes was induced in overnight fasted rats by intraperitoneal (i.p.) injections of 40 mg kg(-1) streptozotocin (STZ) and 100 mg kg(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Liu’s study showed that the increase of body iron could also active AKT and FoxO1, which are important regulators of Pdx-1 (18). These results suggested that hepcidin would also play a role in the regulation of insulin synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Liu’s study showed that the increase of body iron could also active AKT and FoxO1, which are important regulators of Pdx-1 (18). These results suggested that hepcidin would also play a role in the regulation of insulin synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Total protein was extracted from whole-liver tissues as previously described [ 17 ]. Briefly, 50 mg of tissues was lysed in RIPA buffer, and the protein concentration was determined with a Pierce™ BCA Protein Assay Kit (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The ER is an organelle that plays a key role in nutrient metabolism. Our previous study showed that iron supplementation (>1 g ferric iron/kg diet) increased ER stress responses and impaired insulin signaling pathways in a rat model of streptozotocin/nicotinamide-induced diabetes [ 17 ]. ER stress-associated mechanisms are also required for ferritin-mediated macrophage [ 18 ] and hepatic stellate cell activation [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total protein was extracted from whole‐liver tissues as previously described . In brief, 50 mg of tissues was lysed in RIPA buffer, and the protein concentration was determined using a Pierce BCA Protein Assay Kit (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%